Effect of Deposition Time of Mn on Photoelectrochemical Properties of Mn/TiO2 Nanotubes - Kadim Ayal, Asmaa; Mohammed Farhan, Ahlam; Lim, Ying-Chin (International Journal of Engineering and Technology, 2019)
Coupling of TiO2 nanotube arrays (NTAs) with narrow band gap materials has been a promising strategy to extend the absorption of TiO2 into visible light region. In this work, the fabrication of manganese doped TiO2 nanotube arrays (Mn/TiO2 NTAs) was carried out by an electrodeposition method. The deposition time of Mn onto TiO2 NTAs which was varied in the range of 1-5 minutes was found to play an important role in controlling the formation and distribution of Mn nanoparticles onto TiO2 NTAs. The films were characterized by field emission scanning electron microscopy (FESEM), X-ray diffractometry (XRD), energy dispersive X-ray spectroscopy (EDX) and UVâ€“vis diffuse reflectance spectroscopy to determine their morphology, crystalline structure, and optical properties of the samples. The results from FESEM showed that Mn nanoparticles were found to grow larger and cause blockage to the mouth of the nanotubes with prolongs deposition time. On the other hand, Mn/TiO2 NTAs synthesized with shorter deposition time exhibits significant enhancements in the optical absorption and photocurrent density. In particular, the Mn/TiO2 NTAs produced at 1minute deposition time exhibited the highest photocurrent density compared to the others. The uniform distribution and quantity of the Mn could be the reason for this performance, therefore, more light was absorbed and generating more electron-hole pairs then giving the highest photocurrent.Â